2012
DOI: 10.1017/s0033291712000335
|View full text |Cite
|
Sign up to set email alerts
|

First-episode psychosis at the West Bologna Community Mental Health Centre: results of an 8-year prospective study

Abstract: The IR of FEP found by the Bologna study is lower than that found by other European studies. However, as in other studies, the incidence was higher in certain groups. This heterogeneity has implications for policy and mental health service development, and for understanding the aetiology of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 35 publications
(46 reference statements)
6
42
1
2
Order By: Relevance
“…Improving this is critical and should be regarded as a high priority [92]. Various studies have reported a higher risk of psychiatric disorders such as depression, anxiety, suicidal behavior and psychosis among immigrants [1,10,17,19,52,83,108,114,118,119]. Factors such as loneliness, homesickness, loss of status, language problems, resident permit status, unemployment, poverty, low education, poor living conditions, open racism and dissonance between norms and values of the country of origin and the receiving country, can all play an important role [8,13,14,36,42,98].…”
Section: Migration Minorities and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving this is critical and should be regarded as a high priority [92]. Various studies have reported a higher risk of psychiatric disorders such as depression, anxiety, suicidal behavior and psychosis among immigrants [1,10,17,19,52,83,108,114,118,119]. Factors such as loneliness, homesickness, loss of status, language problems, resident permit status, unemployment, poverty, low education, poor living conditions, open racism and dissonance between norms and values of the country of origin and the receiving country, can all play an important role [8,13,14,36,42,98].…”
Section: Migration Minorities and Mental Healthmentioning
confidence: 99%
“…The wider social determinants of their health (including mental health) are often different from those of the settled community and may require health care professionals to use a different approach [8,12,16,56]. We know that culture plays an important role in the symptom presentation of distress and illness and, moreover, that cultural factors have quite an impact on the diagnostic process and the treatment strategies in all populations [3,39,77,101,108,122]. Cultural competence is one concept that has been advanced as a way of capturing the capacity to provide appropriate care for diverse patients, overcoming socio-cultural differences and other systemic challenges to reduce disparities with regard to mental health care provision [6,16,79,91,117,129].…”
Section: Introductionmentioning
confidence: 99%
“…The migratory flow has mainly headed in the last decade to the Northern Italian regions, among which Emilia-Romagna region was one of the most open to newcomers that currently total 11.9% of the population (http://statistica.regione.emilia-romagna.it/servizi-online/ statistica-self-service/popolazione/popolazione-residentestraniera, accessed 1 December_2013). Despite these significant social and demographic changes, to our knowledge only few studies have been conducted on immigrants' mental health and service utilisation, some of which in Bologna (Tarricone et al 2009(Tarricone et al , 2011(Tarricone et al , 2012a(Tarricone et al , 2012bSpigonardo et al in press). In particular, differences in service use between Italians and immigrants have not been extensively investigated, with few exceptions (Gaddini et al 2008;Piazza et al 2010;Tarsitani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report a higher incidence of psychotic disorders in immigrant populations when compared to native populations [1-4]. Epidemiological studies about the incidence of severe mental disorders in migrants, as well as the identification of specific vulnerabilities and stressors associated with migration, have significantly contributed to the development of models explaining the etiopathogenesis of psychosis in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have investigated the risk factors for the onset of psychotic disorders in migrants in Italy [4,27]. Here health care is provided to the population by the Italian National Health Service, which is built like the British National Health Service.…”
Section: Introductionmentioning
confidence: 99%